Faktor-Faktor yang Mempengaruhi Disclosure Serta Dampaknya terhadap Cost of Equity Capital - Sri Hermuningsih (Sinergi: Kajian Bisnis dan Manajemen, 2012)
The purpose of this study was to analyze the disclosure impact on the cost of equity capital companies listed on the Indonesia Stock Exchange. The population in this study were categorized LQ45 companies and is listed on the Indonesia Stock Exchange and the financial statements have been audited since 2006-2010, the number of samples was 182 companies. The statistical method used to test the hypothesis is Structural Equation Modeling (SEM). The results showed that: (1) investment opportunity set has positive and significant impact on disclosure (2) size has positive and significant impact on disclosure disclosure and significant negative effect on the cost of equity capital.Keywords: investment opportunity set, size, disclosure, cost of equity capital